EFFECT OF GROWTH REGULATORS ON SEEDLINGS GROWTH OF APRICOT (PRUNUS ARMENIACA L.) - KURDI, ROZHEEN H. SHABAAN; AL-ZEBARI, SULAIMAN M. KAKO (Journal of Duhok University, 2022)
This study was conducted during the growing season of 2021 and 2022 in horticulture station located at Akre city center Duhok Iraqi Kurdistan region, the study was aimed to investigate the effect of growth regulators on seedling growth of apricot and determined the best concentration of Gibberellin, Benzyl adenine and Kinetin to improve vegetative growth of seedling of apricot . so it consisted of three concentration of GA3 (0, 250 and 500 mg.L-1), BA (0,150 and 300 mg.L-1), KIN (0,150 and 300 mg.L-1) on some vegetative growth characteristics of apricot seedlings (Prunus armeniaca L.).The best results include the following. apricot seedlings sprayed with different concentrations of GA3 significantly affected and gave the seedling height, number of leaves, dry weight, single leaf area and total chlorophyll. Also, seedling sprayed with different BA concentration effected significantly and gave the highest seedling diameter, number of leaves, single leaf area, and dry weight. Whereas seedling spray with different KIN concentrations significantly affected on seedling diameter and total chlorophyll. Generally, interaction between GA3 and KIN and interaction between GA3 and BA and the interaction between BA and KIN was effected significantly on most growth parameters. The best result was in the treatment (GA3 500 mg.L-1 + BA 300 mg.L-1 + KIN 150 mg.L-1) which significantly affected on all growth parameters (seedling height, seedling diameter, single leaf area, total chlorophyll, number of leaves and dry weight)